Optimalisasi Parameter Proses Injeksi Menggunakan Simulasi Moldflow untuk Meminimalkan Cycle Time dan Eliminasi Short Shot pada Produk Tempat - Anwar, M. Choirul; Budiyantoro, Cahyo; Thoharudin, Thoharudin (JMPM : Jurnal Material dan Proses Manufaktur, 2018)
Plastic materials in the manufacture of food and household appliances have been widely used by the public. Various forms and functions have been made, one of which is using an injection molding machine. With an injection molding machine a packaging design or a fairly complex household appliance can be produced. One of the products that the market is interested in is a traditional rice container. This traditional rice container product uses polypropylene material. In this rice container production process there are several problems, namely the cycle time that is too long and the occurrence of short shots on the product. Of these problems, simulations and optimizations that have been carried out provide better results. Optimization carried out in this study is the process parameters using moldflow simulation. Confirmation based on S / N Ratio analysis, ANOVA on the best parameters, after the optimization simulation is obtained from the previous time 172.59 seconds to 23.88 seconds. Short shot and cavity weight obtained increased from 96.99 grams to 99.36 grams.